Penerapan Akuntansi Murabahah Dan Akuntansi Musyarakah Dalam KPR BTN iB (Studi Kasus Pada Bank BTN Syariah Cabang Malang) - Kresna Syukma Taruna; Nining Ika Wahyuni; Bunga Maharani (UPT Penerbitan Universitas Jember, 2019)
This study aims to analyze the application of murabahah accounting and musyarakah accounting applied by Bank BTN Syariah Branch Malang in home financing product purchase. The method used is qualitative method with primary data source that is to interview to related parties and secondary data source obtained from literature and Financial Report of Bank BTN Syariah Branch of Malang. This research refers to Statement of financial accounting standards (PSAK) which have been issued by Bank Indonesia and has been commonly applied by banks in Indonesia. The conclusions of this study indicate the accounting treatment and implementation in the use of mortgage financing BTN iB according to PSAK and Fatwa National Sharia Board MUI. However, Bank BTN Syariah Branch Malang is not fully in accordance with the National Sharia Board Fatwa MUI and Statement of financial accounting standards (PSAK). There were some points which were not in line such as when there was a purchasing, bank did not buy the productm but only financed it. Other things were not in line were recognition and measurement of down payment, discount and number of account receivables which were presented in financial report. In terms of accounting musyarakah there were some points which were not in line, such as recognition on loss and receivables on profit and loss sharing.Keywords: KPR BTN iB, Murabahah Financing, Musyarakah Financing, PSAK.